Selective Laser Trabeculoplasty for Glaucoma Secondary to Emulsified Silicone Oil after Pars Plana Vitrectomy: A Pilot Study. (13th April 2014) - Alkin, Zeynep; Satana, Banu; Ozkaya, Abdullah; Basarir, Berna; Altan, Cigdem; Yazici, Ahmet Taylan; Demirok, Ahmet
Abstract : Background . To investigate the efficacy of selective laser trabeculoplasty (SLT) for lowering intraocular pressure (IOP) in patients with open angle glaucoma (OAG) secondary to emulsified silicone oil (SO). Methodology/Principal Findings . Prospective, interventional, consecutive case series of 11 eyes with sustained elevation of IOP after SO removal. The mean IOP at baseline, week 1, month 1, month 3, and month 6 was evaluated. The mean baseline IOP was significantly decreased from 25 ± 2.7 mmHg to 18.4 ± 5.5 mmHg at week 1 ( P = 0.01 ), 17.9 ± 3.1 mmHg at month 1 ( P = 0.008 ), 15.8 ± 3.9 mmHg at month 3 ( P = 0.003 ), and 16.2 ± 4.7 mmHg at month 6 ( P = 0.004 ) . IOP < 21 mmHg was achieved in 91% of the eyes without a significant complication at month 6. Conclusion/Significance . SLT may be successful for lowering IOP in patients with OAG secondary to emulsified SO which was not controlled with maximum antiglaucomatous medical treatment.